No longer qualified? Changes in the supply and demand for skills within occupations - Mary A. Burke; Alicia Sasser; Shahriar Sadighi; Rachel B. Sederberg; Bledi Taska (Federal Reserve Bank of Boston, 2020)
Using a novel database of 159 million online job postings, we examine changes in employer skill requirements for education and specific skillsets between 2007 and 2017. We find that upskilling - in terms of increasing demands for bachelor's degrees as well as software skills - was a persistent trend among high-skill occupations, but either a temporary or non-existent phenomenon among middle-skill and low-skill occupations. We also find evidence that persistent upskilling in the high-skill sector contributed to greater occupational mismatch that remained elevated during the recovery from the Great Recession. In contrast, labor market mismatch had largely dissipated within the low-skill and middle-skill sectors by 2017.
Keywords: D22; E24; J23; J24; J63; 330; labor demand; skills; vacancies; unemployment; firm behavior